Muslim women and patriarchy: Struggles and resistance in the short stories of Randa Jarrar and Shaila Abdullah - Zafira Hasna Indah; Hasnul Insani Djohar (Universitas Dian Nuswantoro, 2026)
This study discusses how the Muslim female main characters in Randa Jarrar’s short stories, “Accidental Transients and The Life, Loves”, and “Adventures of Zelwa the Halfie” (2016), and Shaila Abdullah’s “Amulet for the Caged Dove” and “Ashes to Ashes, Dust to Dust” (2005), experience the struggles with patriarchal constraints. Moreover, this study examines how the Muslim female main characters resist the very patriarchal system that confines them. This study aims to reveal how patriarchy adversely impacts Muslim women’s lives, how their patriarchal experiences are shaped, and their agency in liberating themselves. A descriptive qualitative method was employed using comprehensive textual analyses to examine the selected issues. This study employs several feminist theories, including Sylvia Walby’s theory of Patriarchy, to explore how the Muslim female main characters’ struggles are presented, and Kimberlé Crenshaw's theory of Intersectionality to investigate how their gender intersects with their diverse social identities. In addition, James Scott’s theory of Resistance is employed to examine how the Muslim female main characters resist patriarchy. The findings show that there is a private form of patriarchy perpetuated by both men and women within the short stories. Furthermore, patriarchal experiences occur due to the interaction between gender and cultural background, and the Muslim female main characters’ resistance is illustrated through positive self-affirmations, self-perceptions, and eventually leaving the patriarchal environment. As a result, this study contributes to raising awareness of the struggles that Muslim women must face due to patriarchy and promotes Muslim women’s empowerment in overcoming its adverse impact through resistance.